The Value of Folklore Characters in Literacy Reading Materials in Elementary School - Lili Agutina; Isna Kasmilawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Instilling character values in the present is very necessary to overcome the moral crisis, especially in the phase of children and adolescents. This research was conducted so that teachers can know the character values contained in folklore and can use folklore as a learning medium that will be used during literacy learning in elementary schools. The approach used in this study is qualitative descriptive research method. Research methods that contain data quotations to give an overview of the presentation of research. The type of research used is library research. The source of data in this study is South Kalimantan Folklore and Nusantara Folklore published by Pustaka Sandrojaya. The data collection techniques used are literature study techniques and text observation techniques. The results showed that character values in the folklore of South Kalimantan and Nusantara found seven character values. The seven character values are 1) The character value of friendship that can be found in the folklore entitled Magic Crocodile and Suri Ikun, 2) The value of hard work character that can be found in the folklore entitled Pangeran Samudera, Putri Junjung Buih, The Story of Nini Kudampai and Si Angui, Galuh Rumbayan Amas, Malin Kundang and Timun Emas, 3) The value of social care characters that can be found in the folklore entitled Pangeran Samudera, Putri Junjung Buih, Putri Niwer Gading, Ular n'Daung, Suri Ikun and Si Putri Malam, 4) The value of environmentally caring characters that can be found in folklore entitled Asal MulaTelaga Biru and Buaya Ajaib, 5) The character value of responsibility that can be found in folklore entitled Pangeran Samudera dan Putri Junjung Buih, 6) The value of discipline character that can be found in the folklore entitled Putri Junjung Buih, and 7) The value of the curious character that can be found in the folktale entitled The Princess of the Night. Based on the character values found, the value of socially caring characters is the most common value found in folklore.